THE FIRST BEETLES (PERMOSYNIDAE, COLEOPTERA) FROM THE UPPER TATARIAN OF EUROPEAN RUSSIA - Ponomarenko A.G. (My University, 2003)
Isolated beetle elytra from the upper Tatarian of the Aristovo locality (Vologda Region) are described as Permosyne dentata sp. nov. and P. europaea sp. nov. (organ-family Permosynidae). This is the first find of beetles in the upper Tatarian of European Russia. The distribution of beetles in the uppermost Permian and the composition of the family and genus are discussed.
Keywords: Permosynidae; Coleoptera; upper Tatarian; European Russia; Paleozoic::Permian::Lopingian; Палеозой::Пермская::Лопинский